Boosting microbial electrocatalysis via localized high electron shuttles concentration by monolithic electrode based on nanostructured nitrogen-doped carbon microtubes - Tao, Le (2022)
Electrode materials capable of increasing the electricigens loading and accelerating the extracellular electron transfer (EET) are urgently required for microbial electrocatalytic technologies. In this work, a monolithic electrode (MDC800AM) based on three-dimensional (3D) interconnected N-doped carbon microtubes (NCMTs) derived from nanostructured polyaniline (PANI)-coated cotton fibers is prepared by a facile and scalable method. The PANI-coating layer and subsequent manganese (Mn)-catalyzed graphitization is helpful in doping the surface with nitrogen atoms and improving its graphitization degree, which contributes significantly to the hydrophilicity, biocompatibility and electronic conductivity of the electrode. Because of the hollow structure and large inner diameter of NCMTs, the MDC800AM is able to buffer the electrolyte facilitating well-localized electron shuttles (ES) within the electrode region as well as increase the surface area for electricigens to inhabit. Based on these advantages, the as-prepared MDC800AM exhibits enhanced microbial electrocatalytic activity and stability such as to outperform its counterpart made up of solid carbon fibers. This work not only provides a monolithic electrode manifesting greatly accelerated activity toward microbial electrocatalysis, but also a proof-of-concept demonstration of boosting the microbial fuel cell (MFC) performance via localized high ES concentration.